PENGARUH ENVIRONMENTAL, SOCIAL DAN GOVERNANCE TERHADAP KINERJA KEUANGAN : (STUDI PADA PERUSAHAAN SEKTOR ENERGI, KESEHATAN DAN INSFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Kurniawan, Aceng; Muhammad Ihsan Syahir, (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract. The purpose of this study is knowing the influence of Environmental, Social and Governance on financial performance. The population in this study were companies in the energy, health and infrastructure sectors listed on the IDX during the 2019-2023 period with a total of 196 companies. The sample selection was carried out using purposive sampling method, so that 125 observation data were obtained that met the predetermined criteria. this study uses Stakeholder Theory as a theoretical basis, and applies a quantitative approach with multiple linear regression models. The analysis techniques used include descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis testing which are tested using the SPSS version 26 software application. The results of this study indicate that Environmental has a positive effect on financial performance. while for Social and Governance each has a negative effect on financial performance.